2021
DOI: 10.3390/biom11111559
|View full text |Cite
|
Sign up to set email alerts
|

Variant Aldehyde Dehydrogenase 2 (ALDH2*2) as a Risk Factor for Mechanical LA Substrate Formation and Atrial Fibrillation with Modest Alcohol Consumption in Ethnic Asians

Abstract: Aldehyde dehydrogenase 2 (ALDH2) rs671 polymorphism is a common genetic variant in Asians that is responsible for defective toxic aldehyde and lipid peroxidation metabolism after alcohol consumption. The extent to which low alcohol consumption may cause atrial substrates to trigger atrial fibrillation (AF) development in users with ALDH2 variants remains to be determined. We prospectively enrolled 249 ethnic Asians, including 56 non-drinkers and 193 habitual drinkers (135 (70%) as ALDH2 wild-type: GG, rs671; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…A recent study in Asians showed that ALDH2*2 increased the risk of atrial fibrillation in habitual drinkers, suggesting that there may be synergistic effects of ALDH2*2 and chronic alcohol consumption on cardiac arrhythmias ( 10 ). To investigate whether ALDH2*2 was associated with higher risk of CAD in chronic drinkers, we examined genetic information and drinking status of human participants from the UK Biobank ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in Asians showed that ALDH2*2 increased the risk of atrial fibrillation in habitual drinkers, suggesting that there may be synergistic effects of ALDH2*2 and chronic alcohol consumption on cardiac arrhythmias ( 10 ). To investigate whether ALDH2*2 was associated with higher risk of CAD in chronic drinkers, we examined genetic information and drinking status of human participants from the UK Biobank ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, alcohol consumption is a well-known risk factor for CAD ( 8 ). Although ethanol is not a primary contributor to CAD in studies of non-Asian individuals, it may have a substantial effect on ALDH2*2 carriers of Asian descent ( 9 , 10 ). Thus, it is important to determine the combined effect of ALDH2*2 and alcohol consumption on CAD to develop preventative strategies to reduce CAD risk among ALDH2*2 carriers.…”
Section: Introductionmentioning
confidence: 99%
“…ALDH2 plays a vital function in resisting oxidative stress by reducing reactive oxygen species and eliminating reactive aldehydes produced by lipid peroxidation, such as 4-hydroxy-2-non-enal (4-HNE) ( 14 16 ). Undoubtedly, oxidative stress plays an important role in the occurrence of AF ( 17 ) and is contained in the pathophysiological process for certain cardiovascular diseases which induce AF ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 249 Asians, modest alcohol consumption was associated with an accumulation of 4-hydroxy-trans-2-nonenal (4-HNE), an ROS-generated aldehyde adduct, prolonged PR interval in the ECG, and a reduction in echocardiographic peak atrial longitudinal strain (PALS) and phasic strain rates. In individuals with ALDH2 polymorphism, an increased association between the daily alcohol intake and LA ejection fraction, PALS and phasic reservoir, and booster functions was observed [ 155 ].…”
Section: Atrial Myocardium and Alcoholmentioning
confidence: 99%